Analysis Of Financial Feasibility And Business Development Strategy Of Oyste Mushroom Bag Log As a Effort To Overcomefarm Labour Poverty At Jember Regency - Tidar Aden Hawa; Qory Zuniana (AGRIBEST, 2020)
Jember regency is  faced  with the problem of high poverty rate. Poor population were  dominated by farm laborers. The free time they have every day is an opportunity to find additional job. Paguyuban "Agro Karunia Mulya" (AKM) located in Arjasa, Jember Regency, is a farmer group of oyster mushroom bag log. The purpose of this research is to know whether the Paguyuban AKM oyster mushroom bag log is feasible or not, and to find the right strategy for developing oyster mushroom bag log in the effort to overcome the poverty of farm workers in Jember Regency. The feasibility use NPV analysis, IRR, Net B/C, and PP. The sensitivity measured using sensitivity analysis. Development strategy use SWOT analysis. The NPV value is Rp. 426.676.573, IRR is 74%, Net B/C is 3.28. Payback Period (PP) is 2 years 4 months 8 days, it means oyster mushroom bag log at AKM community is feasible to run. The oyster mushroom bag log business is not sensitive to 20% raw material cost increase and is still feasible to proceed. The development strategy of AKM community are:  improvement human resources quality with education and training of baglog cultivation, entrepreneurship management, maximize agricultural labor absorption thereby helping to over come the poverty of farm laborers. Building partnership with farm laborers who wants to cultivate oyster mushroom  is also needed.